Therapeutic adherence in elderly citizens with high blood pressure and type 2 diabetes: A qualitative approach - Aedo Romero, Viviana (2021)
Aim: To explore and describe the dimensions that affect the therapeutic adherence of elderly patients with high blood pressure and/or type 2 diabetes in Araucanía, Chile. Methods: This was a qualitative, ethnographic, and descriptive research that addressed its content analysis following Bardin. It corresponds to the first phase of an exploratory study in which two focus groups are carried out; the participants were 12 people over 70 years of age with hypertension and/or type 2 diabetes. Results: Thirteen emerging categories are described: three are in vivo (being a burden for others, getting help using the cellphone, and impoverished life), and ten are theoretical (ageism, isolation and loneliness, popular culture to control the pathology, matriarchal family structure, deep-rooted biomedical model, underestimation of the non-medical team, unfulfilled expectations paradox, importance of social participation, self-care, incomplete and fragmented adherence, and risk of decompensation). Conclusion: The ageism, isolation and loneliness categories present a greater cardiovascular risk due to the difficulty that people who suffer loneliness have to adhere to the treatment. The aid relationship is weakly described, and the biomedical paternalism prevails. It is necessary to strengthen participatory strategies in the cardiovascular program, and activities based on the needs of the elderly.